Monday

April 21, 2014

April 21, 2014

Posted by **melek** on Sunday, February 19, 2012 at 7:52pm.

4^(2x − 1) = 6

- pre-cal -
**Bosnian**, Sunday, February 19, 2012 at 10:54pmlog ( a ^ n ) = n * log ( a )

( 2 x - 1 ) * log ( 4 ) = log ( 6 ) Divide both sides by log ( 4 )

2 x - 1 = log ( 6 ) / log ( 4 )

2 x = log ( 6 ) / log ( 4 ) + 1

2 x = log ( 6 ) / log ( 4 ) + log ( 4 ) / log ( 4 )

2 x = [ log ( 6 ) + log ( 4 ) ] / log 4

2 x = log ( 24 ) / log ( 4 ) Divide both sides by 2

x = [ log ( 24 ) / log ( 4 ) ] / 2

x = log ( 24 ) / 2 log ( 4 )

Remark:

log ( a ) + log ( b ) = log ( a * b )

log ( 4 ) + log ( 6 ) = log ( 6 * 4 ) = log ( 24 )

**Related Questions**

pre-cal - Find the solution of the exponential equation, correct to four decimal...

math - Find the solution of the exponential equation 7+(5^5x)=25 correct to at ...

Pre-Cal - 1) Solve the equation exactly for x: log3 x - log3(x-3) = 2 I got 1 as...

Pre-Cal - Convert the given exponential function to the form indicated. Round ...

pre-calculus - solve the equation 1. In x + In (x+12) =2 x= ? or either there is...

pre-calculus - solve the exponential equation. express the solution in terms of ...

exponential equation-Algebra - Solve the exponential equation. Express the ...

Pre calculus - Okay, I'm really fuzzy about my log and exponential chapter. For...

Pre-cal - 1) Find two values of Q that satisfy the equation. Give your answer ...

pre-cal - can anyone please explain to me how to simplify this exponential ...